Transfemoral Transcatheter Mitral Valve Implantation With a Dedicated Device in a Rheumatic Mitral Stenosis Patient - Lauren S. Ranard, MD; Brett E. Grizzell, MD; Torsten P. Vahl, MD; Juan F. Granada, MD; Bassem M. Chehab, MD (JACC: Case Reports, 2023)
A 65-year-old obese woman with rheumatic heart disease and restrictive lung disease presented with decompensated heart failure. Evaluation demonstrated severely thickened mitral valve leaflets, severe mitral stenosis, and moderate mitral regurgitation. She underwent successful transfemoral transseptal transcatheter mitral valve replacement with a dedicated valve resulting in improved functional status. (Level of Difficulty: Advanced.)